Pengembangan Trainer Aplikasi Multi-Sensors (TAMS) Berbasis Arduino dan Raspberry Pi - Muhammad Yusro; Mufti Ma’sum; Marie Muhamad; Ariep Jaenul (Risenologi, 2021)
At the higher education level in the field of engineering, the development and utilization of educational media for practical learning is needed to ensure that students have technical skills and not just theory. The purpose of this study is to develop practical learning media for the transducer sensor subject and industrial instrumentation in the Multi-Sensor Application Trainer (TAMS). The trainer is based on current developments in transducer sensor technology and control systems. The research method used is research and development (R & D) using a media development model with ADDIE (analysis, design, development, implementation, and evaluation). Developing this trainer includes making hardware (hardware) and software (software). This trainer has various sensors, outputs, and a control module in the Arduino Mega2560 and is supported by the Raspberry Pi. This trainer is equipped with a practicum module that contains 15 (fifteen) practicum that will be used by students. The results of the validity test by material experts obtained an average percentage of the assessment score of 85.25% which means that it is valid and very feasible to use. The results of the validity test by media experts obtained an average percentage of the assessment score of 78.04%, which means that it is valid and very feasible to use. The results of the student's assessment of the use of trainers are 90%, so it can be concluded that the TAMS is very suitable for use. Qualitatively, students considered that the TAMS could function well and be easy to use.